The rise of trapped populations - Humble, A (Refugee Studies Centre, University of Oxford, 2014)
As border security increases and borders become less permeable, cross-border migration is becoming increasingly difficult, selective and dangerous. Growing numbers of people are becoming trapped in their own countries or in transit countries, or being forced to roam border areas, unable to access legal protection or basic social necessities.